INTRODUCTION TO GEOGRAPHY EDUCATION BASED ON EXPLORATION OF THE SURROUNDING ENVIRONMENT FOR EARLY CHILDREN - Pratama, Hendra (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore and analyze critical aspects of Geography Education that can be applied to early childhood. The main focus of this research involves the concepts of location, human interaction, movement and area as the main pillars of geography learning for early childhood based on exploration of the environment around the school as the first introduction and interaction with the real (natural) environment. The literature review research method was used to investigate theories related to geography education, characteristics of early childhood, and relevant geographic skills. Through literature analysis, this research details the importance of understanding home location, place identity, and human interactions as a basis for the development of early childhood characteristics. The conclusions of this study include a synthesis of literature findings, identifying knowledge gaps that need further exploration, and suggesting further research directions. The results of this research contribute to an in-depth understanding of how to develop geography learning methods that suit the needs and characteristics of young children. The practical implications of these findings can help educators and educational practitioners in designing interesting and effective teaching strategies, creating a strong foundation for the development of geographical understanding in the early stages of children's development.